The complexity of outsourced services and the role of international business travel. (28th September 2016) - Liu, Runjuan; Scholnick, Barry; Finn, Adam
Abstract: We hypothesize that face-to-face communication between international business partners is a valuable mechanism for reducing transaction costs, even in contexts where electronic communication is pervasive. Specifically, we examine whether face-to-face interactions (as measured by international business travel) have greater impacts where transaction costs are higher, e.g., where services with greater complexity are outsourced offshore. Matching data from the Survey of International Air Travelers with Bureau of Economic Analysis data on U.S. service outsourcing, we find that international business travel leads to more outsourcing of more complex services. We further provide evidence on the differential role of international business travel by showing that: (i) business travel by managers leads to relatively more outsourcing of more complex services and (ii) business travel by non-diaspora members leads to relatively more outsourcing of more complex services.